Analisis Pendapatan Pengrajin Perak di Desa Kamasan Kabupaten Klungkung - Arifini, Kadek; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 6, Juni 2013 (pp. 277-313), 2013)
The development of industry in Bali is focused on micro industry development, and one of the well known handicrafts in Bali is silver handicraft. Bali is a micro industry producer of silver handicraft that has already well known in foreign countries. This research is aimed to analyze the influence of independent variables comprises of product, working hours, and working experiences simultaneously and partially toward dependent variables namely silver handicrafts’ income in Kamasan Village of Klungkung Regency. The data analysis results indicate that product, working hours, and working experiences simultaneously have significant influence toward silver handicrafts’ income in Kamasan Village of Klungkung Regency with Adjusted R Square value of 0,567. Partially, in one hand, working hours is found to have no significant influence toward silver handicrafts’ income; on the other hand, the number of products and working experiences is found to have significant influence toward silver handicrafts’ income in Kamasan Village of Kulung Regency.
Keywords: Income, the number of product, working hours, working experiences.